Does Star Power Sell? Celebrity Endorsements and Consumer Purchase Intentions in Rupandehi, Nepal - Marasini, Arju; Upadhyaya, Tara Prasad (Journal of Business and Social Sciences Research, 2025)
This study investigated how celebrity endorsements drive purchase intention in Nepal’s Rupandehi district, analysing attributes like trustworthiness and congruence. Based on data from 384 respondents, regression analysis revealed that congruence, familiarity, and liking are the key drivers of consumer purchase intention. Notably, attributes such as trustworthiness and expertise were found to have an insignificant effect. The findings indicate that congruence is the strongest predictor, underscoring the critical need for marketers to select celebrities whose public image and values are in strong alignment with the brand’s identity to effectively influence consumer behaviour.